2021
DOI: 10.1111/ajag.13021
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of health‐related quality of life in older New Zealanders with cardiovascular health problems

Abstract: Objective With longer life expectancies, cardiovascular diseases are increasingly common among older adults, which also leads to functional changes that severely impact their quality of life. This study aimed to identify the predictors of health‐related quality of life (HRQOL) among older New Zealanders with cardiovascular health problems. Methods A cross‐sectional data analysis of the 2015/16 New Zealand Health Survey was performed. In total, 2203 older New Zealanders with cardiovascular health problems were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The last finding regards the significant direct association observed between physical activity behavior and HRQoL, both evaluated at final follow-up. This result is consistent with prior research that already showed a significant impact of being regularly physically active on patients’ cardiovascular health (Adorni et al, 2022; Arija et al, 2018; Hawkes et al, 2013; Montayre et al, 2022). Notably, the present study adds complexity to this association by estimating significant indirect effects of baseline HRQoL and cardiac self-efficacy evaluated 18 months before.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The last finding regards the significant direct association observed between physical activity behavior and HRQoL, both evaluated at final follow-up. This result is consistent with prior research that already showed a significant impact of being regularly physically active on patients’ cardiovascular health (Adorni et al, 2022; Arija et al, 2018; Hawkes et al, 2013; Montayre et al, 2022). Notably, the present study adds complexity to this association by estimating significant indirect effects of baseline HRQoL and cardiac self-efficacy evaluated 18 months before.…”
Section: Discussionsupporting
confidence: 93%
“…Particularly among patients with CVDs, significant relationships were evidenced between perceived HRQoL and the adoption of health behaviors. Prior studies revealed that adopting and maintaining adequate physical activity levels contributed to obtaining both short- and long-term positive effects (up to 3 years after the coronary event) on perceived cardiovascular health (Adorni et al, 2022; Arija et al, 2018; Montayre et al, 2022). Similarly, findings from another longitudinal research revealed that more frequent sedentary behaviors predicted lower levels of both physical and mental HRQoL over 6 months (Hawkes et al, 2013).…”
mentioning
confidence: 99%